Метод вибрационно-импульсного диагностирования технического состояния зубчатых передач - Гаврилов, Сергей Алексеевич; Ишин, Николай Николаевич; Гоман, Аркадий Михайлович; Скороходов, Андрей Станиславович (НТУ "ХПИ", 2016)
Уточнен расчет параметров ударного импульса на основе учета упругости валов и подшипников зубчатой передачи. Приведены результаты экспериментальных исследований нагруженности зубьев прямозубой зубчатой передачи для различных значений нагрузок и скоростей. Уточнение значений параметров ударного импульса позволяет повысить достоверность оценки ресурса зубчатой передачи трансмиссионных узлов мобильных машин.

Clarifies the calculation of parameters of shock pulse by taking into account the stiffness of shafts and gear bearings. The experimental results of loading of spur gear teeth for different loads and speeds values are obtained. Clarification of shock pulse parameters allows to increase the accuracy of resource assessment units of mobile machines gear transmission. Offered in the calculation according to the "Joint Institute of Mechanical Engineering of the National Academy of Sciences of Belarus" of use in the development of the method vibration and pulse diagnosis of technical condition and residual life of gears transmission systems of mobile machines in operation.
The method of vibration-pulse diagnosing of a technical condition of gears
Keywords: зубчатая передача; виброимпульс; ударная сила; время удара; shock pulse; vibration diagnostics